1966
DOI: 10.1139/p66-259
|View full text |Cite
|
Sign up to set email alerts
|

The Thermal Conductivity of Platinum Between 300 and 1 000 °k

Abstract: The thermal conductivity of high-purity platinum was measured between 300 and 1 000 °K. The results obtained agree very well with the previously reported work of Bode and of Martin and Sidles, but at higher temperatures are in definite disagreement with the results of Powell and Tye. The observed variation of the thermal conductivity with temperature implies that at high temperatures the (electronic) Lorenz number of platinum is an increasing function of temperature, exceeding in magnitude the Sommerfeld value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

1966
1966
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 1 publication
0
8
0
2
Order By: Relevance
“…The general problems connected ~vith heat leakage along the input \\ires of a central heater of the type used in this experiment have already been described (see Appendix of Laubitz and van der Meer 1966). Specifically, however, the arrangements of the input leads that \\re have here employed differed froin those used previously in a manner which simplifies the analysis; rather than using long leads ~vhich exchange heat only radially wit11 the environment, \\e have tied these leads thermally to the guard only a short distance (1.4 cm) from the central heater.…”
Section: Appendixmentioning
confidence: 99%
“…The general problems connected ~vith heat leakage along the input \\ires of a central heater of the type used in this experiment have already been described (see Appendix of Laubitz and van der Meer 1966). Specifically, however, the arrangements of the input leads that \\re have here employed differed froin those used previously in a manner which simplifies the analysis; rather than using long leads ~vhich exchange heat only radially wit11 the environment, \\e have tied these leads thermally to the guard only a short distance (1.4 cm) from the central heater.…”
Section: Appendixmentioning
confidence: 99%
“…Its transport properties are important and closely related with each other [8,9] and, thus, extensive studies are reported for Pt at ambient pressure [10][11][12][13][14][15][16][17][18][19][20][21][22][23]. For example, the electrical resistivity, the Seebeck coefficient, and the thermal conductivity are reported to be 10.87 μ cm, −5.28 μV/K, and 71.6 W m −1 K −1 at 300 K, respectively [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…By using K n , the electrical resistivity ρ, the Seebeck coefficient S, and the thermal conductivity k can be calculated as follows, [10], the Seebeck coefficient [11], the thermal conductivity [12], and the Lorenz number [10,12]. Cross symbols are previous experiments of resistivity [13,14,[16][17][18][19], Seebeck coefficient [15][16][17]20,21], and thermal conductivity measurements [14,18,22,23]. Open gray circles indicate the previous calculation [33].…”
Section: Introductionmentioning
confidence: 99%
“…As there is Pt as the transducer [25] and Si as the substrate, the heat equation of multiple layers was used for further analysis. The temperature-dependent properties of Nb 2 O 5 [26], Pt [27][28][29] and Si [29][30][31] were based on values from the literature. The values for α of Nb 2 O 5 resulted from the fit are presented in Figure 4.…”
Section: Analytical Solution Of Fourier's Law To Evaluate Thermal Difmentioning
confidence: 99%